Women's perceived susceptibility to and utilisation of cervical cancer screening services in Malawi - Melanie Y. Hami; Valerie J. Ehlers; Dirk M. van der Wal (AOSIS, 2014)
Background: Malawi provides cervical cancer screening services free of charge at some public health facilities. Few women make use of these cancer screening services in Malawi and many women continue to be diagnosed with cervical cancer only during the late inoperable stages of the condition. Objectives: The purpose of this study was to discover whether the perceived susceptibility to cervical cancer, amongst Malawian women aged 42 and older, influenced their intentions to utilise the available free cervical cancer screening services. Method: A quantitative, cross-sectional descriptive study design was adopted. Structured interviews were conducted with 381 women who visited 3 health centres in the Blantyre District of Malawi. Results: A statistically-significant association existed between women's intentions to be screened for cervical cancer and their knowledge about cervical cancer (X² = 8.9; df = 1; p = 0.003) and with having heard about HPV infection (X² = 4.2; df = 1; p = 0.041) at the 5% significance level. Cervical cancer screening services are provided free of charge in government health institutions in Malawi. Nevertheless, low perceived susceptibility to cervical cancer amongst women, aged 42 and older, might contribute to limited utilisation of cervical screening services, explaining why 80% of cervical cancer patients in Malawi were diagnosed during the late inoperable stages. Conclusion: Malawian women lacked awareness regarding their susceptibility to cervical cancer and required information about the available cervical cancer screening services. Malawi's women, aged 42 and older, must be informed about the advantages of cervical cancer screening and about the importance of effective treatment if an early diagnosis has been made. Women aged 42 and older rarely attend antenatal, post-natal, well baby or family-planning clinics, where health education about cervical cancer screening is often provided. Consequently, these women aged 42 and older should be informed about cervical screening tests when they utilise any health services. Vroue se vermeende vatbaarheid en benutting van servikale kanker dienste in Malawi  Agtergrond: Malawi verskaf gratis servikale kanker siftings dienste by sommige openbare gesondheids instansies. Min vrouens maak gebruik van die kanker siftings dienste in Malawi en baie vrouens word steeds gediagnoseer met servikale kanker tydens die laat onopereerbare fases van die toestand. Doelwitte: Die doel van die studie was was om te bepaal of Malawiese vrouens wat 42 en ouer is se waargenome vatbaarheid vir servikale kanker hulle beïnvleod om beskikbare gratis servikale siftingsdienste te gebruik. 'n Kwantitatiwe, deursnee beskrywende navorsingsontwerp was gekies. Metode: Gestruktureerde onderhoude is met 381 vrouens gevoer wat drie gesondheidsdiensentrums in die Blantyre Distrik van Malawi besoek het. Resultate: 'n Statistiese beduidende verhouding het bestaan tussen vrouens se voornemens om vir servikale kanker getoets te word en hulle kennis oor servikale kanker (X² = 8.9; df = 1; p = 0.003) en dat hulle al gehoor het van MPV infeksies (X² = 4.2; df = 1; p = 0.041) op die 5% vlak van beduidenis. Servikale kanker siftingsdienste is gratis beskikbaar in openbare gesondheidsdiensinrigtings in Malawi. Desnieteenstaande was daar 'n lae waargenome risiko van servikale kanker onder vrouens wat 42 jaar oud en ouer was en dit het bygedra tot die beperkte benutting van siftingsdienste, wat verduidelik waarom 80% van servikale kankergevalle in Malawi gedurende die laat onopereerbare fases gediagnoseer is. Gevolgtrekkings: Malawiese vrouens was onbewus van hulle vatbaarheid vir servikale kanker en het inligting benodig oor servikale kanker siftingsdienste. Malawi se vrouens wat 42 jaar oud en ouer is, moet ingelig word aangaande die voordele van servikale sifting en die belangrikheid van effektiewe behandeling indien 'n vroë diagnose gemaak is. Vrouens van 42 of ouer benut selde voorgeboorte, nageboorte gesonde baba, of gesinsbeplanningsklinieke waar voorliging aangaande servickale kanker verskaf word. Gevolglik behoort die vrouens ingelig te word oor servikale siftingstoetse wanneer hulle enige gesondheidsdienste benut.